COVID-19 in 2020 – a look back from NHS frontline - Smith, Julie; Collier, Toni; Dixon, Karen; Adebusuyi, Morenike; Sikabofori, Tonye; Cameron-Taylor, Michaella; Baikie, Toyin; NG, Cho Ee; Akinkunmi, Akintunde; Guillum-Scott, Suzanne; Moscrop, Dot; Adedeji, Olufunso (Journal of Global Medicine, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or COVID-19 defined our world in 2020. In over a year since the World Health Organization (WHO) declared the COVID-19 outbreak a pandemic, on 11th March 2020, over 130 million people have contracted the virus worldwide, of whom 2.9 million have died. Healthcare systems have weathered unprecedented stresses, but the modern medical and technological advances have come up with vaccines within a year of the WHO declaration. Consequently, as healthcare workers look forward to more normal and less stressful times, some United Kingdom National Health Service (NHS) colleagues have had a retrospective look at their experiences at the beginning of the pandemic.